Identifikasi Prednison dan Piroxicam dalam Jamu Pegel Linu di Yogyakarta dengan Metode Kromatografi Lapis Tipis - Burhan, Amelia Handayani; Irianto, Iramie Duma Kencana; Indraswari, Laksita Putri; Saputri, Lintang Handoyo (Politeknik Kesehatan Bhakti Setya Indonesia, 2024)
Herbal medicine (Jamu) is a part of Indonesian cultural heritage passed down through generation. One of the commonly consumed “Jamu” in Yogyakarta is “Jamu Pegal Linu” (herbal medicine for aches and pains). Competition among “Jamu” producers often leads to the addition of chemicals subtances to enhance the drug’s effectiveness. This practice is strictly prohibited due to its potential adverse health effects. Prednisone and piroxicam, which are pharmaceutical compounds, are suspected to be frequently added to “Jamu Pegal Linu”. Therefore, this study aims to identify the presence of prednisone and piroxicam in “Jamu Pegal Linu” available in Yogyakarta. Sampel of “Jamu Pegel Linu” were collected using a purposive sampling method from herbal shops in the Yogyakarta area. The samples were extracted using 96% ethanol. The extracted samples were then spotted onto a TLC plate, which was placed in a saturated chamber. The mobile phase used to identify prednisone were ethyl acetate: chloroform in ratios of 9:1, 6:4, and 8:2; whereas for piroxicam, three mobile phases were used: chloroform : acetone (80: 20), ethyl acetate : methanol : ammonia (60: 30: 10), and chloroform : methanol (100: 5). The stationary phase used was a silica gel GF254 plate. A sample was considered positive if the Rf value and the color of the spot of the spot matched those of the reference standard. The results of the study, using the thin-layer chromatography (TLC) method, showed that none of herbal medicine samples for aches and pains circulating in the Special Region of Yogyakarta contained prednisone or piroxicam. Therefore, the analyzed herbal medicine samples are considered safe for public consumption.